Micromorphological Characteristics and Origin Analysis of Contact Metamorphic Coal - Jianxin HUANG; Yanfei AN; Zheng HAN; Shuyang HE; Shuo ZHENG; Bingxiang LIU (Yankuang ceshi)
BACKGROUNDDuring tectonic movements and geological activities, coal seams are destroyed and engulfed by magma, which not only accelerates the slow carbon cycling process in geological history, but also changes and disrupts the carbon cycling balance of the lithosphere at that time. As a global period of tectonic magmatism in the Mesozoic, the Yanshan period magma intruded into the Mesozoic coal-bearing basins and intruded and engulfed coal seams on a large scale.OBJECTIVESTo reveal the process and reasons for the change of contact metamorphic coal micromorphology during the process.METHODSContact metamorphic coal samples with different degrees of thermal metamorphism at the periphery of the Yuandian Ⅱ mine in northern Anhui Province were collected and subjected to coal quality analysis, organic fraction separation, GC-MS, polarized light microscopy (PLM) and scanning electron microscopy (SEM).RESULTSToward the rock, the contents of volatile, hydrogen, nitrogen and soluble organic matter of the sample decreases; ash yield and mirror group reflectance increases; relative content of naphthalene series decreases; relative content of phenanthrene series among soluble aromatics increases. The microfractions of unaffected coal and shallow thermal metamorphic coal consist mainly of colloidal structural bodies, and the latter is fracture developed. The natural coke is composed mainly of mosaic structure with irregularly shaped devolatilized pores, and the pore sizes range from 20µm×50µm to 50µm×150µm. The magma coke is composed mainly of porous carbon and carbon microspheres: the porous carbon is rich in round-elliptical pores, the pore sizes range from 0.5 to 3µm, and the carbon microspheres are developed on the fissures and the inner wall of the pores.CONCLUSIONSTending to the rock, the degree of thermal metamorphism of coal seams continues to increase: Shallow thermally metamorphosed coals are the products of brittle fracture of coal seams subjected to weaker thermal metamorphism; Natural coke is the result of volatile fraction removal and plastic deformation of shallow thermally metamorphosed coals; Magma coke is the result of further intermediate phase transformation of natural coke by magma. Therefore, the change of contact metamorphic coal micromorphology is considered to be caused by the process of thermal alteration, devolatilization and intermediate phase transformation of coal rock components.